Investigating the mechanical behavior of composites made from textile industry waste. Issue 5 (4th May 2017) - Umar, Muhammad; Shaker, Khubab; Ahmad, Sheraz; Nawab, Yasir; Umair, Muhammad; Maqsood, Muhammad
Abstract: Recycling the waste for environmental protection has been an important challenge for the mankind. The fibrous waste in textile industry accounts for approximately 15% of the amount of fibers used, leading to a lower yield %. The current study focused to use this waste as reinforcement to produce a fiber-reinforced polymer composites. Reinforcements were woven in 3/1 S twill, using yarn produced from noil waste and knitting waste in the weft direction. The weft yarn count, type of waste material and number of picks were the variables of study. Laminated composites were fabricated from these reinforcements and the mechanical properties (tensile, bending and impact) were compared to the conventional glass fiber composites. The specific mechanical properties of these composites were found comparable or less than that of glass fiber composites.